The future of shows with live animals in Colombia - Javier Ernesto Baquero Riveros (Universitat Autonoma de Barcelona. Facultat de Dret, 2017)
The Colombian Constitutional Court declared UNENFORCEABLE article 5 (partial) of Law 1774 of 2016 which, referring to Article 7 of the Animal Protection Statute, exempted from criminal sanctions for animal mistreatment the behavior descriptions in the latter (rejoneo, coleo, bullfights, novilladas, corralejas, heifers, tientas, cockfights and related procedures). It considers that the reference made by Law 1774/16 suffers from indeterminacy (Principle of Legality), it does not know the Principle of Typicity and reproduces material contents declared unconstitutional, all of which generates a deficit of constitutional protection towards the animals. However, the effects of the Judment differed for the term of two (2) years for the Congress of the Republic to adapt the legislation to Constitutional jurisprudence.